ANALISIS KEPUASAN SISWA/SISWI DAN CITRA SEKOLAH SMK KELING KUMANG SEKADAU - Bertus, Adil; Elvi, Fitria (STIE 'INDONESIA' Pontianak, 2025)
Vocational High School is an upper secondary school that forms students / students when they finish school to be ready to go down to the world of work. The number of schools both private and public offers various advantages of each school, this study aims to see student satisfaction with the services provided by the school and the image of SMK Keling Kumang school in the community. The results of the research based on the survey that has been conducted can be concluded that overall the students of SMK Keling Kumang are satisfied with the services provided by the school and according to the community based on the survey results and discussion that the school image of SMK Keling Kumang is categorized as good, this is evidenced by several question instruments used in this study.